2020
DOI: 10.3390/ijms21072274
|View full text |Cite
|
Sign up to set email alerts
|

Developing Computational Model to Predict Protein-Protein Interaction Sites Based on the XGBoost Algorithm

Abstract: The study of protein-protein interaction is of great biological significance, and the prediction of protein-protein interaction sites can promote the understanding of cell biological activity and will be helpful for drug development. However, uneven distribution between interaction and non-interaction sites is common because only a small number of protein interactions have been confirmed by experimental techniques, which greatly affects the predictive capability of computational methods. In this work, two imba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Dephosphorylation of MLC results in cell relaxation. The catalytic activity of MLCP are inhibited by the phosphorylation of MYPT1 at multiple sites by several kind of kinases, therefore, led to decreased dephosphorylated MLC and thus, vascular smooth muscle contraction (Qiao et al, 2014;Chang et al, 2016;Gao et al, 2017;Deng et al, 2020). The current study found that miR-126 decreased phosphorylation levels of MYPT1 in palmitate-treated HUVECs, which may account for the observed decrease in MLC phosphorylation.…”
Section: Discussionsupporting
confidence: 55%
“…Dephosphorylation of MLC results in cell relaxation. The catalytic activity of MLCP are inhibited by the phosphorylation of MYPT1 at multiple sites by several kind of kinases, therefore, led to decreased dephosphorylated MLC and thus, vascular smooth muscle contraction (Qiao et al, 2014;Chang et al, 2016;Gao et al, 2017;Deng et al, 2020). The current study found that miR-126 decreased phosphorylation levels of MYPT1 in palmitate-treated HUVECs, which may account for the observed decrease in MLC phosphorylation.…”
Section: Discussionsupporting
confidence: 55%
“…Given these limitations, the models generated here must be considered preliminary and incomplete. Other predictive tools, such as predictions of protein interactions based on molecular structure, specific groups, may be good cross-validations (Deng et al, 2020 ; Hu et al, 2020 ). Further studies should also be done to illustrate the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…XGBoost was used on the benchmark dataset. XGBoost can automatically learn the optimal missing value according to the training loss and more effectively process different types of sparse patterns in the data, which is more stable for different batches of training [ 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%